Interactions of Phytoestrogens with Estrogen Receptors α and β (III). Estrogenic Activities of Soy Isoflavone Aglycones and Their Metabolites Isolated from Human Urine - Tsuchihashi, Ryota; Aomori, Tohru; Okabe, Hikaru; Hirose, Toshiharu; Kinjo, Junei; Nohara, Toshihiro; Morito, Keiko; Nagao, Tsuneatsu; Masamune, Yukito (Biological & pharmaceutical bulletin, 2004)
Two glucuronides (4′-O-, and 7-O-) and a glucuronyl (7-O-) sulfate (4′-O-) of genistein, two glucuronides (4′-O-, and 7-O-) and a glucuronyl (7-O-) sulfate (4′-O-) of daidzein, 7-O-glucuronides of glycitein, dihydrodaidzein and O-desmethylangolensin were isolated from the urine of volunteer subjects fed soy bean curds (Tofu). The estrogenic activities, i.e., i) the effect on the estrogen-dependent growth of MCF-7 cells, ii) the binding ability to human estrogen receptors (hERs) α and β, and iii) the effect on hER-dependent β-galactosidase induction, of these isoflavone metabolites were examined. Two synthetic isoflavone aglycones (dihydrodaidzein and O-desmethylangolensin) and four synthetic sulfates (4′-O- and 4′-, 7-di-O-) of genistein and daidzein were also studied for their estrogenic activities for the purpose of comparison. With respect to estrogenic acivity, the tested isoflavone metabolites were classified into three groups. The first group shows a very poor stimulatory effect toward the growth of MCF-7 cells, binding activity, and β-galactosidase induction. The sulfates belong to this group. The second group shows a moderate binding activity but poor stimulation and β-galactosidase induction. Some glucuronyl conjugates belong to this group. The last group shows a moderate stimulation and β-galactosidase induction but poor binding activity. A mixed type of conjugates having glucuronyl and sulfony moieties belong to this group.